The Impact of Cumulative Risk on Criminal Behavior Across the Life Course - TenEyck, Michael F. (Journal of developmental and life-course criminology, 2023)
Individuals are differentially exposed to risk factors and the causes of criminal behavior vary from person to person. Evidence supports the idea that we should track exposure to individual risks. There is, however, less research examining whether risk factors converge to produce a cumulative effect. The current study uses Add Health data to examine both the distinct and cumulative effects of myriad theoretically informed risk factors on criminal behavior. Results reveal that certain risk factors such as drug/alcohol use, victimization, as well as prior delinquency are consistent predictors of criminal behavior across the life course. But when risks are considered cumulatively, a nonlinear association emerges wherein the predicted rate of delinquency increases dramatically when going from one to two standard deviations above the mean. We propose that it may be time to consider taking a “risk-factor-wide” approach to the study of criminal behavior.